Bioengineered surgical repair of a chronic oronasal fistula in a cat using autologous platelet-rich fibrin and bone marrow with a tailored 3D printed implant. Issue 9 (September 2018) - Soares, Carla S; Barros, Luís C; Saraiva, Virgínia; Gomez-Florit, Manuel; Babo, Pedro S; Dias, Isabel R; Reis, Rui L; Carvalho, Pedro P; Gomes, Manuela E
Clinical summary: A tissue engineering approach was used to aid the surgical repair of a chronic oronasal fistula (ONF) in a 13-year-old cat. A three-dimensional (3D) printed mesh, tailored to the size and shape of the ONF, was created to support a soft tissue flap used to close the defect; and also to provide a matrix for mesenchymal stromal cells present in bone marrow aspirate and bioactive cytokines and growth factors present in platelet-rich fibrin harvested from the patient. A CT scan at day 75 after surgery revealed the formation of new tissue in the defect and the healing process was complete at follow-up 6 months after surgery. Relevance and novel information: Complications are frequently reported following surgical repair of ONFs and include dehiscence of the palatal suture line, flap necrosis due to damage to the greater palatine artery and maxillary osteomyelitis, mainly due to chronic infection and bone lysis. The case described here demonstrates how input from a multidisciplinary team and the use of a biomaterial, processed by sophisticated technologies, can create a precision regenerative medicine strategy adapted to the patient's clinical needs; this provided a novel therapeutic solution for an otherwise hard to treat clinical problem.